Chinese film festivals : sites of translation - Berry, Chris ; Robinson, Luke (Palgrave Macmillan, 2020)
This book is the first anthology of research devoted to the booming world of Chinese film festivals, covering both mainstream and independent films. It also explores festivals in the Chinese-speaking world and festivals of Chinese films in the rest of the world. The book asks how Chinese film festivals function as sites of translation, translating Chinese culture to the world and world culture to Chinese-speaking audiences, and also how the international film festival model is being transformed as it is translated into the Chinese-speaking world.Introduction.-.Section 1: Translating the Film Festival.-.A: International Film Festivals in the Chinese Speaking World.-.1. Chris Berry, 'Shanghai and Hong Kong: A Tale of Two Festivals.'.-.2. Elena Pollacchi, ''Mature at Birth': The Beijing International Film Festival between the National Film Industry and the International Film Circuit.'.-.3. Ming-yeh T. Rawnsley, 'Culture Translation between 'Local' and 'International': The Golden Harvest Award Festival in Taiwan.'.-.B: Specialized Independent and Small Film Festivals in the Chinese-Speaking World.-.4. Hongwei Bao, 'Queer as Catachresis: The Beijing Queer Film Festival in Cultural Translation.'.-.5. Flora Lichaa, 'The Beijing Independent Film Festival: Translating the Non-Profit Model into China.'.-.6. Nikki J.Y. Lee and Julian Stringer, ''China's Sundance' and Corporate Culture: Creating Space for Young Talent at the Tudou Video Festival.'.-.7. Esther C.M.  |9 |a Yau, 'What Can Small Festivals Do? Towards Film Festivals as Testimony to Expanded Civic Engagement in Post-handover Hong Kong.'.-.8. Sabrina Qiong Yu and Lydia Dan Wu, 'The China Independent Film Festival and Chinese Independent Film Festivals: Self-Legitimization and Institutionalization.'.-.C: Chinese Film Festivals Outside the Chinese-Speaking World.-.9. Luke Robinson, 'Sole Traders, Cultural Brokers, and Chinese-Language Film Festivals in the United Kingdom: The London Taiwan Cinefest and the Chinese Visual Festival.'.-.Section 2: Translating Culture.-.A: International Film Festivals in the Chinese-Speaking World.-.10. Dina Iordanova, 'Yingying, Zhenzhen and Fenfen? China at the Festivals.'.-.11. Ma Ran, 'Programming China at the Hong Kong International Film Festival and the Shanghai International Film Festival.'.-.12.